Corporate Entrepreneurship dan Innovation PT. Bank Jawa Barat (BJB) Pada System Digital Banking Untuk Mengejar Keunggulan Kompetitif - Tradiga Nur Aziz; Margo Purnomo; Ratih Purbasari (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
Bjb Digi is a mobile banking application owned by the Regional Development Bank of West Java and Banten (bjb). Bjb digi is a mobile application that is integrated on smartphones based on Android, Blackberry, and iOS operating systems. Indonesia has 4 Persero Commercial Banks, 35 Foreign Exchange Private Commercial Banks, 30 Non-Foreign National Private Commercial Banks, 15 Joint Venture Banks, 10 branch offices of Foreign Banks, and 26 Regional Development Banks. This research is in the form of a qualitative descriptive study aimed at describing and interpreting the object analyzed according to the actual situation. The research subject in this study is “Corporate Entrepreneurship and Innovation PT. West Java Bank (BJB) on the digital banking system to pursue competitive advantage. The object of the research is BJB Digi which is used for the mobile banking system at PT. West Java Bank (BJB). To see the advantages of Bank BJB's mobile banking system, precisely in 2020. Corporate Entrepreneur Actions at PT. Bank Jawa Barat Tbk such as Sustainable Regeneration, Organizational Rejuvenation, Strategic Renewal and Domain Redefinition.